Translating the Representation of Malabo in the United States and Spain: The Case of Paul Theroux’s The Lower River - Martín Matas, Patricia (Miscelánea: A Journal of English and American Studies, 2024)
In this paper we analyze how Malabo and Africa appear represented in the novel The Lower River, by American author Paul Theroux, and how his cultural and linguistic vision of- the city and the continent reach Spain through the translated version. In order to do so, a description of the publishing market is provided to understand its importance both for the original text and for the translation in Spain. Through a textual analysis of both texts using the software Wordsmith Tools (Scott 2004), including word-frequency and concordance searches, we will explore if there is a positive or negative portrayal of Malabo. Finally, through a linguistic comparative analysis of the original and the translation, we will determine to what extent the reader in Spain can draw the same inferences as the English reader of the original.